Biocompatibility of injectable hydrogel from decellularized human adipose tissue in vitro and in vivo. Issue 5 (23rd October 2018) - Zhao, Yu; Fan, Jun; Bai, Shuling
Abstract: Adipose tissue engineering is considered as a promising treatment for repairing soft tissue defects. The decellularized extracellular matrix (ECM) is becoming the research focus in tissue engineering for its tissue specificity. In this study, the human adipose tissue liposucted from healthy people were decellularized by a series of mechanical, chemical, and enzymatic methods. The components of cell and lipid were effectively removed, whereas the collagens and other ingredients in adipose tissue were retained in the human decellularized adipose tissue (hDAT). Then the extracted hDAT was further fabricated into injectable hydrogel, which could be self‐assembled to form gel under certain condition. The hDAT hydrogel was nontoxic to human adipose‐derived stem cells (ADSCs) and could spontaneously induce adipogenic differentiation in vitro. It was highly biocompatible and could not cause inflammation and rejection after being implanted subcutaneously. The hDAT hydrogel developed in this study will be one of the available choices for soft tissue enlargement and cosmetic fillers because of its noninvasive in collection and implantation process. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1684–1694, 2019.